الإجارة المنتهية بالتمليك - Umair, Kuswoyo Abu; Rosyadi, Imron; Badri, Muhammad Arifin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research focuses on fiqh issues disputed by the Syafi'i Madzhab Ulema with the Three Other Madzhab Imams in the book of Ijarah Muntahiyah Bittamlik and the results of the decision of the Indonesian Ulema Council on this issue. Which is taken from the collection of fatwa decisions of the Indonesian Ulema Council and the book Ahkamul Fuqoha'. The aim of this research is to provide a clear description of the fiqh issues that are disputed by those in the Ijarah book and the reasons for their differences, and to explain the influence of the legal decisions of the Syafi'i madzhab on these issues with the legal decisions of the Indonesian Ulema Council. This research is descriptive qualitative library research using comparative methods. The findings in this problem are that the opinions of the Shafi'i madzhab in the book of Ijarah have an influence on the fatwas of the Indonesian Ulema Council in the law of Ijarah Muntahiyah Bittamlik. The reasons for differences of opinion between the two in the book of Ijarah Muntahiyah Bittamlikare: differences in the assessment of a hadith, the rules of proposal, ijtihad using qiyas, and the meaning of Arabic lafadz. In this matter, the opinion of the Indonesian Ulema Council is in accordance with the Shafi'i school of thought on these two issues. The issues disputed by them are matters of ijtihadiyyah; therefore, they should not be the cause of division, and it is permissible to follow the opinions of different scholars in the sect, but considering a difference to be acceptable does not prevent it from explaining the truth, so for a Muslim from among A student of Sharia knowledge is obliged to follow the opinion that he considers to be correct, while a layman is obliged to take the opinion of the person whom he considers to be the most pious and the most virtuous. Key words: Ikhtilaf,Ijarah Muntahiyah Bittamlik, Indonesian Ulema Council, and four schools of thought